Open moral communities - Mandelbaum, Seymour J. (MIT Press, 2000)
Seymour Mandelbaum's extended reflection on communities and the myths that sustain them is a plea for a communitarian sensibility. Communities are critically important in maintaining and adapting public moral orders. Seymour Mandelbaum's extended reflection on communities and the myths that sustain them is a plea for a communitarian sensibility. Communities are critically important in maintaining and adapting public moral orders. To do so, they must recruit, socialize, and discipline members; distinguish between members and strangers; collect resources; and cultivate a domain of competence. The communitarian sensibility is a disposition to assess the impact of innovative opportunities and compelling moral claims on the design, repair, and dissolution of communities and communal fields with a healthy skepticism about unlikely strategies. The book is divided into three parts. The first part sets out the role of communities in the creation of moral orders and discusses the implications of three prevalent myths about community. The second part discusses six terms--theory, story, time, city, tool, and plan--that figure prominently in both professional and lay constructions of public orders. The third part presents two cases in which ambiguous moral claims for redemption and justice challenge the pluralism of the open myth. One concerns exclusionary zoning in New Jersey, the other the 1985 attack on the MOVE compound in West Philadelphia. Mandelbaum's blending of moral philosophy and concrete examples concludes with an account of citizenship in liberal republics.